(untitled) (Advancements in Homeopathic Research, 2024)
Homeopathic pharmacy is a specialized field within the broader realm of pharmacy that revolves around the principles and practices of homeopathy [1]. Dr. Samuel Hahnemann invented homeopathy in the late 18th century. It is a holistic medical system based on the concept that “like cures like” and emphasizes individualized treatment tailored to the patient’s unique symptoms [2]. In the context of homeopathic pharmacy, the term encompasses the identification, collection, preservation, specific preparation techniques, combining, compounding and standardization of medications [3]. It also covers the general operating knowledge of the pharmaceutical industry and how various preparations get distributed [4]. A holistic therapeutic approach of homeopathy primarily utilizes medicinal plants in its pharmaceutical preparations. The collected medicinal plants undergo